Potential Evaluation of Oil Palm Frond Juice for The Production of Bioethanol - Mior Ahmad Khushairi, Mohd Zahari; Dhiyatul Ridhwan, Md Nasarudin (2013)
Fossil fuels degrade abundantly since the 21st century.